Humoral and T-Cell-Mediated Immunity Against Phlebotomus perniciosus Salivary Proteins in Dogs from a Leishmaniosis-Endemic Area - Núria Balsells-Aguilar; Maria Magdalena Alcover; Marta Baxarias; Alejandra Álvarez-Fernández; Lourdes Alarcón; Petra Sumova; Petr Volf; Laia Solano-Gallego (Pathogens)
Compounds in sand fly saliva elicit specific immune responses that may play a role in the establishment of canine Leishmania infection. Although canine antibodies to anti-sand fly saliva antigens have been extensively studied, little is known about cellular immune responses against Phlebotomus perniciosus salivary proteins. This study aimed to explore humoral and T-cell-mediated immunity against P. perniciosus salivary proteins in dogs (n = 85) from Mallorca (Spain), a leishmaniosis-endemic area, and find correlations with demographic (age, sex, and breed) and parasite-specific immunological parameters. Anti-sand fly saliva IgG was examined using a P. perniciosus whole salivary gland homogenate (SGH) ELISA and recombinant salivary protein rSP03B ELISA. Interferon gamma (IFN-γ) release whole blood assays with L. infantum soluble antigen (LSA), SGH, and rSP03B were also performed. Positive correlations were found between IgG levels in the SGH and rSP03B tests and between concentrations of SGH IFN-γ and rSP03B IFN-γ. While concentrations of SGH IFN-γ and rSP03B IFN-γ were low and produced only by a minority of dogs (less than 20%), high levels and frequencies of LSA IFN-γ as well as anti-saliva IgG for SGH and rSP03B were detected in a majority of dogs (61% and 75%, respectively). LSA IFN-γ levels were positively correlated with age and Leishmania-specific antibodies. In conclusion, dogs from a leishmaniosis-endemic area presented high humoral immunity against P. perniciosus salivary proteins, but their cellular immunity to these proteins was low and less frequent.